OPTIMASI ALOKASI SISTEM PENGOLAHAN SAMPAH ANORGANIK DENGAN METODE CAPACITATED MAXIMUM COVERING LOCATION PROBLEM - Silalahi, Agustinus; Zefanya, Eva Angelica; Natalia, Christine; Prasetya, Wibawa (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2022)
Province X in Indonesia has a significant problem with trash that has been challenging to address. The Environment Agency therefore desires to construct an inorganic Trash Management System. The Environment Agency has four potential locations with various capacities. The purpose of this research is to locate a trash treatment system's best possible site and allocate each TPS that is less than 30 km and more over 30 km from the chosen system, respectively, to ensure that the overall distance traveled is as little as possible. There are four possible locations, and it required to select three of them. This study use the LINGO 18.0 software to solve the Capacitated Maximum Covering Location Problem (CMCLP) approach. Distance parameters used by CMCLP are split into two stages. The first stage is to determine the location of the trash treatment system to be built and the allocation of trash and the amount of trash from each TPS using Mix Integer Programming. B is not chosen out of the options, which are A, B, C, and D. System A will receive 1,407,520 tons of trash totaling 24 TPS. System C receives trash from 147 TPS weighing 1,294,495 pounds. System D will receive trash weighing 819,142 tons from 88 TPS. The allocation of trash from TPS that are more than 30 km away takes place in the second stage. Three TPS are assigned to System A, and seven TPS are assigned to System D.